2021
DOI: 10.1038/s41598-021-83020-7
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning prediction models for prognosis of critically ill patients after open-heart surgery

Abstract: We aimed to build up multiple machine learning models to predict 30-days mortality, and 3 complications including septic shock, thrombocytopenia, and liver dysfunction after open-heart surgery. Patients who underwent coronary artery bypass surgery, aortic valve replacement, or other heart-related surgeries between 2001 and 2012 were extracted from MIMIC-III databases. Extreme gradient boosting, random forest, artificial neural network, and logistic regression were employed to build models by utilizing fivefold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 24 publications
0
37
0
1
Order By: Relevance
“…In order to improve the nursing quality and make individualized clinical decision, several models of predicting ICU length of stay after CABG have been developed [ 27 , 28 ]. A study built up machine learning models to predict 30-day mortality and three complications in critically ill patients after open-heart surgery (including CABG) from MIMIC III database [ 29 ]. The machine learning model predicted the short-term outcome by window 10 software with more than 30 risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the nursing quality and make individualized clinical decision, several models of predicting ICU length of stay after CABG have been developed [ 27 , 28 ]. A study built up machine learning models to predict 30-day mortality and three complications in critically ill patients after open-heart surgery (including CABG) from MIMIC III database [ 29 ]. The machine learning model predicted the short-term outcome by window 10 software with more than 30 risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Age and CHF were acknowledged as the risk factors influencing the prognosis of patients after CABG [ 6 , 7 , 20 , 31 ]. WBC play an essential role in cardiovascular disease, some studies have found elevated WBC was associated with cardiovascular complications and mortality in patients after CABG [ 29 , 32 ]. Creatinine increased during perioperative stage served as independent risk factor for mortality in patients after CABG, and some risk assessment models after cardiac surgery included creatinine [ 6 , 20 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we integrated data from several datasets, the number of patients and operations is relatively small and needs to be extended. We also faced with the imbalance problem during the study, which is usual for medical data [11]. In such situations machine-learning algorithms tend to classify the data into predominant class.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing these same outcomes, two advanced models (LR and ANN) show even better predictive capability in comparison, with the most significant advantage in predictive power for the ANN model with an AUC of 0.85 (14) (Table 2). In a recent study comparing advanced models reciprocally, an XGBoost model had the upper hand over ANN (18). However, these are outliers in terms of morbidity prediction.…”
Section: Morbidity In the Icumentioning
confidence: 99%